Development Of Interactive Learning Media Based On Websites Using Google Sites On Tax Elements In Class XI Financial Accounting At SMK Negeri 1 Surabaya - Anma Sofyan Wahyudi; Suci Rohayati (Journal of Innovative and Creativity, 2025)
Technological advancements demand innovative learning, yet taxation learning media remain limited and not aligned with the latest regulations. This study aims to develop an interactive learning media based on Google Sites for the topic of Income Tax Article 21 using the Effective Rate (TER) at SMK Negeri 1 Surabaya. The research employed the R&D method using the ADDIE model. Validation results showed an overall feasibility score of 93.44% (subject matter expert 91.33%, media expert 95.56%) categorized as "Highly Feasible." Student responses reached 97.62%, and product effectiveness based on the N-Gain score was 0.89 (categorized as "Very High"). In conclusion, the developed media is highly feasible and effective for use in taxation learning at vocational schools.